The Level VI North-East Temple at Tel Lachish. (2nd January 2019) - Weissbein, Itamar; Garfinkel, Yosef; Hasel, Michael G.; Klingbeil, Martin G.; Brandl, Baruch; Misgav, Hadas
Abstract : During the recent excavations at Tel Lachish a previously unknown Canaanite temple of the 12th century BCE was uncovered in the north-eastern corner of the mound. This article describes its possible place in the urban fabric of the city, the plan of the temple and its parallels, and some of the more special finds that were found in it. Based on the temple's plan and the finds and installations uncovered in it, we wish to offer a glimpse into the cults that were associated with the temple, as well as a reconstruction of the temple's life cycle.